Ḥifẓ al-Nasl and the Inheritance Rights of Non-Marital Children in Indonesia: A Maqâshid Analysis of Constitutional Court Decision No. 46/PUU-VIII/2010 - Nur Azizah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
The issue of inheritance rights for non-marital children remains a significant legal and ethical debate within the Indonesian legal system, particularly following the landmark ruling of the Constitutional Court Decision No. 46/PUU-VIII/2010. This decision recognizes the civil relationship between children born outside of marriage and their biological fathers, creating new legal implications in the field of Islamic inheritance law. However, this recognition has also generated tensions between classical Islamic jurisprudence and contemporary legal developments in Indonesia. This study aims to analyze the inheritance rights of non-marital children through the perspective of maqâshid al-syarî‘ah, particularly the principle of ḥifẓ al-nasl (protection of lineage). This research employs a normative juridical method using a conceptual and case approach by examining statutory regulations, judicial decisions, and classical as well as contemporary Islamic legal scholarship. The findings show that while classical Islamic jurisprudence generally limits lineage affiliation of non-marital children to the mother, the maqâshid framework provides a broader perspective that prioritizes justice, child protection, and social welfare. The Constitutional Court's decision can therefore be interpreted as an effort to protect the civil rights of children while maintaining the essential objectives of Islamic law. This study argues that the maqâshid approach offers a constructive framework to reconcile the tension between Islamic legal principles and contemporary legal developments in Indonesia. Through this perspective, the recognition of certain civil rights for non-marital children may be understood as part of the broader objective of safeguarding lineage, dignity, and social justice within Islamic law. Persoalan hak waris anak non-marital masih menjadi perdebatan hukum dan etika yang signifikan dalam sistem hukum Indonesia, terutama setelah lahirnya Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010. Putusan ini mengakui adanya hubungan perdata antara anak yang lahir di luar perkawinan dengan ayah biologisnya, sehingga menimbulkan implikasi hukum baru dalam bidang hukum waris Islam. Namun demikian, pengakuan tersebut juga memunculkan ketegangan antara konstruksi fikih klasik dan perkembangan hukum kontemporer di Indonesia. Penelitian ini bertujuan untuk menganalisis hak waris anak non-marital melalui perspektif maqâshid al-syarī‘ah, khususnya prinsip ḥifẓ al-nasl (perlindungan terhadap keturunan). Penelitian ini menggunakan metode yuridis normatif dengan pendekatan konseptual dan pendekatan kasus melalui kajian terhadap peraturan perundang-undangan, putusan pengadilan, serta literatur hukum Islam klasik dan kontemporer. Hasil penelitian menunjukkan bahwa meskipun fikih klasik pada umumnya membatasi hubungan nasab anak non-marital hanya kepada ibunya, pendekatan maqâshid memberikan perspektif yang lebih luas dengan menekankan nilai keadilan, perlindungan anak, dan kemaslahatan sosial. Oleh karena itu, Putusan Mahkamah Konstitusi tersebut dapat dipahami sebagai upaya memberikan perlindungan terhadap hak-hak keperdataan anak tanpa mengabaikan tujuan utama syariat. Penelitian ini berargumentasi bahwa pendekatan maqâshid dapat menjadi kerangka konstruktif untuk menjembatani ketegangan antara prinsip-prinsip hukum Islam dan perkembangan hukum kontemporer di Indonesia. Melalui perspektif ini, pengakuan terhadap sebagian hak keperdataan anak non-marital dapat dipahami sebagai bagian dari tujuan yang lebih luas dalam menjaga keturunan, martabat manusia, dan keadilan sosial dalam hukum Islam.